2023
DOI: 10.1002/hbm.26531
|View full text |Cite
|
Sign up to set email alerts
|

The intra‐individual reliability of 1H‐MRS measurement in the anterior cingulate cortex across 1 year

Meng‐Yun Wang,
Max Korbmacher,
Rune Eikeland
et al.

Abstract: Magnetic resonance spectroscopy (MRS) is the primary method that can measure the levels of metabolites in the brain in vivo. To achieve its potential in clinical usage, the reliability of the measurement requires further articulation. Although there are many studies that investigate the reliability of gamma‐aminobutyric acid (GABA), comparatively few studies have investigated the reliability of other brain metabolites, such as glutamate (Glu), N‐acetyl‐aspartate (NAA), creatine (Cr), phosphocreatine (PCr), or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Of note, while metabolite levels in the brain, including those in the dmPFC/dACC, often exhibit remarkable stability over time [90][91][92] , indicating distinct neuro-metabolic phenotypes 93 , they are still susceptible to change. For example, external factors such as stress can dynamically alter glutamate levels in the prefrontal cortex 80,94 , thereby influencing decision-making processes 95,96 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, while metabolite levels in the brain, including those in the dmPFC/dACC, often exhibit remarkable stability over time [90][91][92] , indicating distinct neuro-metabolic phenotypes 93 , they are still susceptible to change. For example, external factors such as stress can dynamically alter glutamate levels in the prefrontal cortex 80,94 , thereby influencing decision-making processes 95,96 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides the time-of-day effect, the seasonal effect on functional brain organization has recently attracted some attention (M. Y. Wang, Korbmacher, Eikeland, & Specht, 2023b;Zhang, Shokri-Kojori, & Volkow, 2023). Specifically, daylight length comes out as a potential contributor (Di, Woelfer, Kühn, Zhang, & Biswal, 2022) to the functional brain organization (M. Y.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, daylight length comes out as a potential contributor (Di, Woelfer, Kühn, Zhang, & Biswal, 2022) to the functional brain organization (M. Y. Wang et al, 2023b). For example, the salience network, one of the resting-state brain networks, is larger when daylight length is short compared to when it is long (M. Y.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Widely used in clinical settings (Oz et al, 2014 ), MRS has recently been applied to identify IDH-mutated gliomas (Branzoli and Marjanska, 2020 ) and explore the association between behavior and MRS-derived neurotransmitters (Li et al, 2022 ). It is suggested that the MRS-derived metabolite estimates are reliable within the participants (Wang et al, 2024 ). In large-scale clinical studies, a multi-site/vendor design is often favored to achieve the necessary statistical power.…”
mentioning
confidence: 99%